Analysis of Merdeka Curriculum Chemistry Textbooks on Atomic Structure Based on Multirepresentation of Chemistry - Nafisah, Aura Zahra; Aini, Faizah Qurrata (Journal of Educational Sciences, 2025)
Atomic structure is a basic topic in chemistry learning that is very important as a foundation for other materials. Understanding this concept requires representations that are able to describe abstract concepts more concretely, with textbooks acting as the main learning resource. Textbooks help learners understand abstract concepts through various forms of representation. However, the chemistry textbooks of the Merdeka Curriculum still show shortcomings, such as the use of inappropriate representations and sourced from the internet. This study analyzes how the representation in the two Merdeka Curriculum chemistry textbooks used in SMA/MA Padang city, with an analysis based on Gkitzia's criteria. The results of this study indicate that chemistry textbooks A and B are dominated by 44% sub-microscopic and 36% macroscopic aspects (C1), in books A and B the surface features of the representations are generally explicit (C2), the representations of books A and B show that they are completely related and linked to the text (C3), in book A the no caption of the representation, while in book B the are existence of problematic caption (C4), books A and B the degree of correlation between representations comprising a multiple one is generally insufficiently linked (C5).